Beautiful Creatures - Garcia, Kami; Stohl, Margie 1967-; Collins, Kevin T.; Bianco, Eve. (New York : Hachette Audio, 2012)
In a small South Carolina town, sixteen-year-old Ethan is powerfully drawn to Lena, a new classmate with whom he shares a psychic connection and whose family hides a dark secret that may be revealed on her sixteenth birthday.
aUnabridged.
aOriginally released in audio format in 2009.
a"Now a major motion picture"--Container.
a"Featuring a conversation with the authors and PDF of the Ravenwood family tree"--Container.
a"Featuring original music by Michele McGonigle"--Container.
aCompact discs.
Keywords: Supernatural -- Fiction; Psychic ability -- Fiction; Love -- Fiction; High schools -- Fiction; Schools -- Fiction; Dreams -- Fiction; Recluses -- Fiction; Audiobooks; South Carolina -- Fiction; South Carolina -- Fiction -- History -- Civil War, 1861-1865; Children's audiobooks